2022
DOI: 10.22495/cgobrv6i2p9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neuromarketing on consumer behaviour

Abstract: One of the biggest interests for companies in today’s market is considered consumer preference, why they make the choice of one product over another. The main aim of this study is to analyse the impact of neuromarketing in the process of identifying the preferences and needs of consumers. Neuromarketing tools provide insights into measuring the effectiveness of advertising campaigns in making an impact on the consumers in online retailing (Singh, 2020). In this study, neuromarketing has been analyzed, understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…Product packaging and product labeling are significant marketing components since they provide valuable information related to the product (Russo et al, 2021). In consonance with past studies, for example, Ismajli et al (2022) suggesting the color of the packaging has a strong influence on the final buying decision, we…”
Section: Future Research Scope In Neuromarketingsupporting
confidence: 72%
See 1 more Smart Citation
“…Product packaging and product labeling are significant marketing components since they provide valuable information related to the product (Russo et al, 2021). In consonance with past studies, for example, Ismajli et al (2022) suggesting the color of the packaging has a strong influence on the final buying decision, we…”
Section: Future Research Scope In Neuromarketingsupporting
confidence: 72%
“…Product packaging and product labeling are significant marketing components since they provide valuable information related to the product (Russo et al, 2021). In consonance with past studies, for example, Ismajli et al (2022) suggesting the color of the packaging has a strong influence on the final buying decision, we propose that the neuromarketing approach may be applied to examine the factors that can help to enhance the effectiveness of product packaging and labeling. For instance, eye‐tracking technology can help future researchers find the impact of the ‘origin of product’ in the products' labeling.…”
Section: Future Research Scope In Neuromarketingsupporting
confidence: 64%
“…Morin (2011) is the reference source. Research has demonstrated that neuromarketing plays a significant role in identifying consumer preferences, enhancing companies' ability to cater to consumer needs more efficiently (Ismajli et al, 2022). Moreover, using neuromarketing tools in hospitality and tourism research is valuable for comprehending consumer behavior and improving customer experiences (Boz & Koc, 2022).…”
Section: Neuromarketing To Improve Customer Experiencementioning
confidence: 99%
“…Behavioural techniques involve the analysis of consumers' behaviours and actions when purchasing, and their interactions with products and brands (Ismajli et al, 2022). These techniques are used to uncover consumers' decision-making or preferences.…”
Section: Source: Authors' Own Developmentmentioning
confidence: 99%